Effect on sperm quality of different cryoprotectants in sperm of Chinchilla lanigera - Gramajo Bühler, María Cecilia (2013)
Summary Chinchilla lanigera is an endangered species therefore the development of cryopreservation protocols for its gametes is a useful tool in the application of assisted reproduction techniques. A study of the functionality of the spermatozoa punctured from the cauda epididymis was performed on fresh or frozen-thawed samples with three cryoprotective media (test-yolk buffer, sucrose and glycerol). The effect that these media had on sperm physiology during the freezing, storage and later thawing process was analysed. A decrease in the percentages of viability, motility, membrane integrity and capacity to undergo the induced acrosome reaction was found with all the media assayed, an increase in the percentages of DNA fragmentation was also observed. The comparative analysis of the effect of the different cryoprotectants assayed showed that the best medium to use to cryopreserve epididymal sperm in this species is test-yolk buffer. This medium had the least effect on the abovementioned physiological parameters, especially at the level of genetic material. Copyright © Cambridge University Press 2012.